The influence of a soldering manner on thermal properties of LED modules. Issue 2 (3rd April 2018) - Górecki, Krzysztof; Dziurdzia, Barbara; Ptak, Przemyslaw
Abstract : Purpose: This paper aims to present the results of the influence of a manner of soldering light emitting diodes (LEDs) to the metal core printed circuit board on thermal parameters of the module LED containing these diodes. Design/methodology/approach: Using the authors' elaborated measuring method and the dedicated measurement set-up, transient thermal impedances of LED modules, mounted using different soldering processes and mounted to the heat-sink with different values of the moment of force, are measured. The obtained results of measurements are discussed. Findings: It was shown experimentally that the manner of soldering could strongly influence efficiency of dissipation of heat generated in the module. The best thermal properties were obtained for soldering using vapour phase technology with vacuum and paste LFS-216LT. It was also proved that the moment of force used while mounting the considered modules on the heat-sink can result in a change of the value of thermal resistance of this module exceeding even 12 per cent. Research limitations/implications: The investigations were performed for five LED modules operating at one, arbitrarily selected value of power dissipated in these modules mounted on the heat-sink of arbitrarily selected dimensions. Practical implications: The obtained results of measurements could be usable for designers of mounting processes of power LED modules. Originality/value: This paper presents the results of investigations of thermal properties of LED modules, in which different techniques of soldering are used. It was shown experimentally that the manner of soldering could strongly influence efficiency of dissipation of heat generated in the module. It was also proved that the moment of force used while mounting the considered modules on the heat-sink is important.